Removal of lead and cadmium from wastewater sludge using bougainvillea sp. through phytoremediation technique / Ahmad Na’im Abdul Rahman, Nurul Nadiah Mohd Firdaus Hum and Zitty Sarah Ismail - Abdul Rahman, Ahmad Na’im; Mohd Firdaus Hum, Nurul Nadiah; Ismail, Zitty Sarah (Universiti Teknologi MARA, 2019)
Phytoremediation uses plants to remove, extract and absorb heavy or toxic matters from soil and water. This study explores Bougainvillea sp. heavy metals uptake capacity under different ratio of wastewater sludge condition. This study used 24 plants of Bougainvillea sp. and involves a duration of 2 months (61 days). The plants were divided and labelled according to six different treatments with four replications; A - Control (100% soil), B (20% sludge), C (40% sludge), D (60% sludge), E (80% sludge) and F (100% sludge). Accumulation of considered metals of lead and cadmium for leaf, stem and roots were analyzed using Inductive Coupled Plasma-Optical Emission Spectrophotometer (ICP-OES). The highest removal was found to be at 60% sludge mixture for both metals. The highest lead and cadmium accumulation were found in the root with the concentration of 0.1 mg kg-1 and 0.06 mg kg-1 respectively. Thus, the optimum lead and cadmium removal using Bougainvillea sp. was at the 60% sludge mixture (Treatment D).